Age at Menarche and Access to Sanitation Facilities as Predictors of Menstrual Hygiene Practices Among Peri‑Urban Adolescents - Lisda Oktavia Madu Pamangin; Helen Try Juniasti; Fajrin Violita (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Menstrual hygiene practices, which are influenced by individual behaviors and environmental conditions, play a crucial role in preventing infection and maintaining reproductive health. This study aimed to analyze the correlation between age at menarche and access to menstrual hygiene facilities with menstrual hygiene practices among adolescent girls living in peri‑urban areas of Jayapura City. An analytic observational study with a cross‑sectional design. A total of 263 school‑aged girls who had experienced menarche were recruited through total sampling. Data were collected using a self‑reported questionnaire measuring menstrual hygiene practices, age at menarche, and access to hygiene facilities. Menstrual hygiene practices were assessed using 20 items with a maximum score of 40, while access to hygiene facilities was measured using five items scored on Likert and Guttman scales. Data were analyzed using Spearman correlation tests. The results showed that the mean age of respondents was 14.51 years, with a mean age at menarche of 12.15 years. The average menstrual hygiene practice score was 28.31, indicating a moderate level of correct hygiene behavior. Most adolescents changed their menstrual pads every 6–8 hours (44.9%), only 17.5% consistently washed their hands with soap after changing pads, and only 17.1% consistently dried the genital area after rinsing. Access to hygiene facilities was generally adequate, with 48.7% having access to clean running water and 84.8% having access to a toilet. Spearman correlation analysis demonstrated a significant positive correlation between age at menarche and menstrual hygiene practice scores (r = 0.147; p = 0.017), as well as between access to hygiene facilities and menstrual hygiene practice scores (r = 0.588; p = 0.000). These findings indicate that earlier menarche and better access to hygiene facilities are associated with improved menstrual hygiene practices. In conclusion, menstrual hygiene practices among adolescents in peri‑urban Jayapura remain suboptimal, although access to hygiene facilities is relatively adequate. Strengthening hygiene education and improving facility availability may enhance menstrual hygiene behaviors and reduce the risk of reproductive tract infections.Keywords: menstrual hygiene; age at menarche; hygiene facility access; adolescent girls; peri‑urban communities